Star Trek the next generation. Terra incognita - Tipton, Scott; Tipton, David (Star Trek. The Next Generation, 2019)
Following their clash with their villainous doubles from the Mirror Universe, the Enterprise crew returns to business as usual, little realizing the serpent in their midst--one of their own has been replaced! Six stories focusing on fan-favorite crew members of the Enterprise-D--including Deanna Troi, Wesley Crusher, and Selar--each connected by the machinations of this sinister doppelganger. What does Mirror Barclay want, and what's to become of his Prime-universe counterpart?! A pulse pounding mosaic of stories from Scott and David Tipton (Star Trek- The Next Generation - Mirror Broken) and artists Tony Shasteen (Star Trek- Boldly Go), Angel Hernandez (Star Trek/Green Lantern), and Carloes Nieto (Star Trek- The Next Generation - Through the Mirror). This volume collects the six-issue series, continuing the saga of one of Star Trek's most popular iterations. These standalone stories mirror the sci-fi mainstay's established history of "done-in-one" episodes, which keep the series accessible to new fans and emphasize original and fascinating ideas. (TM), , & 2018 CBS Studios, Inc. STAR TREK and related marks and logos are trademarks of CBS Studios, Inc. All Rights Reserved.